Hippocampal EUD in primarily irradiated glioblastoma patients - Bodensohn, Raphael; Söhn, Matthias; Ganswindt, Ute; Schupp, Gabriele; Nachbichler, Silke B.; Schnell, Oliver; Belka, Claus; Niyazi, Maximilian (Radiation Oncology, 2014)
Background: Radiation delivery for malignant brain tumors is gradually becoming more precise. Particularly the possibilities of sparing adjacent normal structures such as the hippocampus are increasing. To determine its radiation exposure more exactly, the equivalent uniform dose (EUD) of the hippocampus was compared with further treatment parameters. This way sparing options could be found. Methods: From the database of the University hospital of Munich 61 glioblastoma patients were selected who received primary radiotherapy in 2011. General data about the etiology, treatment course, survival of the patients and dose parameters were retrieved. Results: In a linear regression analysis the side of the tumor (left hippocampus: p < 0.001/right hippocampus: p = 0.009) and its temporal location (left hippocampus: p = 0.015/right hippocampus: p = 0.033) were identified as factors with a significant influence on the EUD of the respective hippocampus. Besides this, the size of the planning target volume (PTV) and the EUD of the hippocampus correlated significantly (p = 0.027; Pearson correlation = 0.291). The median PTV size of the tumor in the right hemisphere was 386.1 ml (range 131.2-910.7 ml), and in the left hemisphere 291.3 ml (range 146.0-588.9 ml) (Kruskal-Wallis test: p = 0.048). A dose quartile analysis showed that 31 patients had a high dose exposure of the hippocampus on one side while having a moderate dose exposure in the other side. Conclusions: The radiation exposure of the respective hippocampus is dependent on the side where the tumor is located as well as on whether it is temporally located. The exposure of the contralateral hippocampus is further dependent on multiple additional factors - nevertheless a reasonable protection seems to be possible in about half of all cases.
CRIS-Team Scopus Importer:2023-09-13
Keywords: EUD; Glioblastoma; Hippocampus; Radiation therapy